Discovery of the centipede family Plutoniumidae (Chilopoda) in Asia: a new species of Theatops from China, and the taxonomic value of spiracle distributions in Scolopendromorpha - Di, Zhiyong; Cao, Zhijian; Wu, Yingliang; Yin, Shijin; Edgecombe, Gregory D.; Li, Wenxin (Zootaxa, 2010)
Theatops chuanensis n. sp. is proposed for a Chinese representative of Plutoniumidae, the first Asian record of this otherwise North American and southern European chilopod family. Its ultimate legs lack prefemoral and femoral spines, and the species is unique within Theatops in possessing spiracles on segment 7. The reliability of segment 7 spiracles as a criterion for diagnosing scolopendromorph genera is challenged by various lines of evidence. An updated key to genera and species of Plutoniumidae is provided.